Idiopathic sudden sensorineural hearing loss and ménière syndrome: The role of cerebral venous drainage. (5th September 2017) - Ciccone, M. M.; Scicchitano, P.; Gesualdo, M.; Cortese, F.; Zito, A.; Manca, F.; Boninfante, B.; Recchia, P.; Leogrande, D.; Viola, D.; Damiani, M.; Gambacorta, V.; et al.
Abstract : Objectives: To evaluate the influence of cerebral venous drainage on the pathogenesis of idiopathic sudden sensorineural hearing loss (ISSHL) and Ménière syndrome (MD). Design: Observational, prospective, cohort study. Setting: ENT and Cardiology Departments (University of Bari, Policlinico Hospital, Bari, Italy). Participants: We enrolled 59 consecutive patients (32 males, mean age 53.05+ 15.37 years): 40 ISSHL and 19 MD. Main outcome measure: All patients underwent physical examination, biochemical evaluation (glycemic and lipid profile, viral serology, C reactive protein, etc), audiometric (tonal, vocal, vestibular evoked myogenic potentials and auditory brainstem response test) and impedentiometric examination. The pure tone average (PTA) was calculated for the following frequencies: 250, 500, 1000, 2000, 3000, 4000, 8000. An echo‐color Doppler evaluation of the venous cerebral veins, internal jugular (IJV) and vertebral veins (VV) at supine and 90° position was performed. Results: No morphological alterations were found both in patients and controls. There were no signs of stenosis, blocked flow, membranes, etc. We found lower minimum, mean and maximum velocities in distal IJVs ( P = .019; P = .013; P = .022; respectively) and left VVs ( P = .027; P = .008; P = .001; respectively) in supine (0°) position in both MD and ISSHL patients as compared to controls. The same was for orthostatic position (90°). We found negative correlations between the velocities in extracranial veins and PTA values: therefore, the worst the audiometric performance of the subjects, the lower the velocities in the venous cerebral drainage. Conclusions: Idiopathic sudden sensorineural hearing loss and Ménière syndrome patients showed altered venous flow in IJVs and VVs as compared to controls, independently from posture. This different behavior of venous tone control can influence the ear performance and may have a role in the pathogenesis of both diseases.